TCP Skudai: A high performance TCP variant for Collaborative Virtual Environment systems - Gital, Abdulsalam Ya’u; Ismail, Abdul Samad; Chiroma, Haruna; Ibrahim, Adamu Abubakar (IEEE, 2016)
In Collaborative Virtual Environment (CVE) systems, one of the main research topics in is how to efficiently transmit message to minimized delay, provide scalability and reliability, and also the choice of transport protocol. TCP is the most widely used protocol in the design of CVE systems, and its throughput deteriorates in the network with large delay due to it conservative congestion control. TCP removes network congestion by adjusting sending rate according to available bandwidth. Researchers have shown that TCP underutilizes bandwidth in a high-speed network and in a long distance network. With the increasing number of concurrent distant collaborators in CVE systems, TCP may not provide the level of consistency and scalability required in the systems. Many researchers have proposed different modifications of TCP, but rarely addressed the issues in CVE systems. In this paper, we proposed a novel TCP variant conceptual model called TCP Skudai, aimed at achieving a high performance congestion control algorithm for CVE systems. The methods used in the conceptualizations lies within adding constraints to the phases of transmission: slow start, congestion avoidance, fast retransmit, and fast recovery based on principle of packet conservation.